Heterologous expression of MirMAN enhances root development and salt tolerance in Arabidopsis - Xu, Juanjuan; Yang, Caiyu; Ji, Shangyao; Ma, Hui; Lin, Jingwei; Li, Hui; Chen, Shuisen; Xu, Hai; Zhong, Ming (Frontiers in Plant Science, 2023)
A mannanase (MAN) gene, namely MirMAN, was cloned from petroleum-tolerant Mirabilis jalapa L. and heterologous-expressed in Arabidopsis. MirMAN protein contains a structural domain specific for glycoside hydrolases. MirMAN is located in the cell wall according to subcellular localization experiments in tobacco leaf cells. Heterologous expression of MirMAN promoted plant growth and development, especially in root development. Meanwhile, heterologous expression of MirMAN reduced the sensitivity of transgenic Arabidopsis to high salt stress and increased the survival rate of plants. The growth rate of wild-type was relatively slow compared with the transgenic plants. In the transgenic plants, antioxidant enzyme activity was significantly increased, reducing the reactive oxygen species level in the plants, while inducing a significant accumulation of soluble sugars and a decrease of lipid peroxidation. Taken together, this study provides the evidence of the protective roles of exogenous endo-β-mannanase activity in the transgenic Arabidopsis response to salt stress, partially via activation of antioxidants and modulation of metabolic homeostasis. The mannanase is a potentially important target gene may be further exploited to improve abiotic stress resistance in plants.